Humanistic Communication Patterns Of Teachers With Special Needs Students In Quran Memorization At Al-Qawiyya School, Karanganyar - Nurul Latifah Nurul Latifah; Sarbini (Jurnal Al-Hikmah, 2024)
This article explores the humanistic communication patterns employed by teachers in assisting special needs students with Quran memorization at Al-Qawiyya School, Karanganyar. Communication serves as a fundamental tool for conveying information and should ideally act as a bridge to strengthen emotional connections, facilitate learning processes, and support Quran memorization. However, in educational settings, particularly those serving special needs students, communication has not received adequate attention, even though these students face unique challenges in emotional, social, and cognitive aspects. This study aims to analyze the humanistic communication strategies applied by teachers to support Quran memorization for students with special needs. The research employs a descriptive qualitative method with a case study approach. Data were gathered through observation, interviews, documentation, and literature review. Findings suggest that an effective communication pattern significantly influences the Quran memorization process for special needs students. The communication strategies used by teachers involve empathetic approaches, verbal and non-verbal communication, interpersonal communication methods, instructional communication, and tailoring approaches to meet the unique needs of each student. This study is intended to serve as a guide for teachers and educators in communicating effectively with special needs students.